1998
DOI: 10.1016/s0014-5793(98)01473-2
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of fibronectin transcription in highly metastatic adenocarcinoma cells

Abstract: Silencing of fibronectin (FN) expression seems to be one of the key mechanisms underlying metastatic behaviour. An inverse correlation exists between FN expression levels and the metastatic potential of two related murine mammary adenocarcinomas, M3 and MM3. Primary cultures of M3 tumour, which is moderately metastatic to lung (40% incidence), show a conspicuous FN extracellular matrix (ECM) and high levels of FN mRNA, while primary cultures of the highly metastatic MM3 tumour (95% lung incidence) are negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…In support of this, we showed that, under serum-starved conditions, the C3.6 cells were less adherent, consistent with ErbB-2 promoting anchorage-independent growth (Harris et al, 1999). The apparent rescue of this adhesion phenotype by plating onto fibronectin (Figure 3) substantiates the notion that ErbB-2 suppression of FN1 plays a functional role in anchorage-independent growth and metastasis, as reported previously (Werbajh et al, 1998;Ignatoski et al, 2000). While our data also suggested that HRGb1 can modify adhesion, and hence the potential for invasiveness, the mechanistic details of this modification are unclear and require further detailed investigation.…”
Section: Discussionsupporting
confidence: 89%
“…In support of this, we showed that, under serum-starved conditions, the C3.6 cells were less adherent, consistent with ErbB-2 promoting anchorage-independent growth (Harris et al, 1999). The apparent rescue of this adhesion phenotype by plating onto fibronectin (Figure 3) substantiates the notion that ErbB-2 suppression of FN1 plays a functional role in anchorage-independent growth and metastasis, as reported previously (Werbajh et al, 1998;Ignatoski et al, 2000). While our data also suggested that HRGb1 can modify adhesion, and hence the potential for invasiveness, the mechanistic details of this modification are unclear and require further detailed investigation.…”
Section: Discussionsupporting
confidence: 89%
“…38 Down-regulation of fibronectin transcription has also been shown to be associated with a highly metastatic form of murine mammary adenocarcinoma cells. 39 These authors demonstrated that loss of fibronectin expression in these cells is not due to changes in the fibronectin promoter sequence but is the result of negative transcriptional regulation. 39 More recent studies using cDNA arrays to identify genes associated with the more metastatic variant of MM3 adenocarcinoma cells as compared to the parent tumor (M3) found that fibronectin was one of only two genes significantly down-regulated among the genes analyzed in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The set of primers used for FN EDI (22), FN EDI minigene (20), and FN IIICS (23) were described previously. The set of primers used for EDII amplification was hEDB-dir (16) and mEDB-rev (5Ј-CAGT-GGACAGTGAATGAGTTGG-3Ј).…”
Section: Methodsmentioning
confidence: 99%